2013
DOI: 10.1021/jo400793a
|View full text |Cite
|
Sign up to set email alerts
|

Development of Asymmetric Deacylative Allylation

Abstract: Herein we present the development of asymmetric deacylative allylation of ketone enolates. The reaction directly couples readily available ketone pronucleophiles with allylic alcohols using facile retro-Claisen cleavage to form reactive intermediates in situ. The simplicity and robustness of the reaction conditions is demonstrated by the preparation of > 6 grams of an allylated tetralone from commercially available materials. Furthermore, use of non-racemic PHOX ligands allows intermolecular formation of quate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Asymmetric deacylative allylation of cyclic ketone enolates with allylic alcohols has been described by Tunge et al Racemic studies with tetralones, substituted at the α‐position by an acetyl group, demonstrated to be better substrates than propanoyl or formyl derivatives for the DaA with different allylic alcohols working with NaH in THF at room temp. (Scheme ).…”
Section: Deacylative Alkylationmentioning
confidence: 97%
See 1 more Smart Citation
“…Asymmetric deacylative allylation of cyclic ketone enolates with allylic alcohols has been described by Tunge et al Racemic studies with tetralones, substituted at the α‐position by an acetyl group, demonstrated to be better substrates than propanoyl or formyl derivatives for the DaA with different allylic alcohols working with NaH in THF at room temp. (Scheme ).…”
Section: Deacylative Alkylationmentioning
confidence: 97%
“…For the asymmetric version of this DaA, different chiral PHOX ligands were assayed . Ligands L1 and L2 gave the best enantioselectivities affording highly enantioenriched α,α‐diallylated tetralones (Scheme ).…”
Section: Deacylative Alkylationmentioning
confidence: 99%
“…Two years later, Tunge et al reported an enantioselective protocol for the allylic alkylation of 1,3-diketones derived from tetralone (Scheme 82). [122] They made use of the PHOX-ligands L6a and L6b, which resulted in acceptable enantiomeric excesses in the allylation products.…”
Section: Allylic Alkylations Of Enolates Formed In 14-additionsmentioning
confidence: 99%
“…27 In 2013, the same group developed the first enantioselective variant of this approach involving the condensation of -diketones 57 with allylic alcohols 58 (Scheme 21). 28 The process is initiated by the addition of the sodium alcoholate to the -diketone 57 liberating a reactive enolate 61 and an allylic acetate 62 (Scheme 21). This allylic acetate is able to undergo activation by the palladium complex generating the required -allyl complex necessary for the eno-late trapping.…”
Section: Short Review Syn Thesismentioning
confidence: 99%